Human urine as a natural attractant of Anastrepha obliqua (Diptera: Tephritidae) - CANAL, NELSON A.; PÉREZ-O., MARIA L.; GONZÁLES, LUISA F. (Revista Colombiana de Entomología, 2010)
The control of fruit flies in Colombia is done with monitoring efforts, with the use of insecticides sprayed or in the form of toxic baits, and with the use of cultural practices. Monitoring is an essential activity and it is done with McPhail traps baited with hydrolyzed protein. As an economical alternative to the use of traps with hydrolyzed protein, this work studied the efficiency of human urine for monitoring fruit flies for small and medium sized fruit producers. Ten treatments were evaluated (urine from women, men and each one mixed at 30, 50 and 70% concentration and the hydrolyzed protein as a control), with four repetitions and in a randomized block design. Multilure® traps were used, hung every 28 m in the national mango collection in the Nataima Research Center located in, Espinal, Tolima, Colombia). Counts of males and females captured in the traps were made twice weekly, and the attractants were replenished weekly. For the females, the developmental stage of the ovaries was determined in order to determine their physiological age (young, mature, old). There was no statistically significant difference in male urine at the concentration of 70% treatment and the hydrolyzed protein; however, the efficiency of the other treatments, with respect to the hydrolyzed protein, was over 40%. In all of the treatments there were greater captures of old females. It is discussed that human urine can be used as an alternative to hydrolyzed protein for the monitoring of this pest by small and medium sized producers.